A Path to Job-Ready Graduates: The Urgency of Curriculum Regulation to Overcome the Competency Gap at State Islamic University (UIN) Jurai Siwo Lampung - Supendi (AMUYA: JOURNAL OF MANAGEMENT, 2025)
This policy paper addresses the urgent need for curriculum reform to bridge the competency gap among graduates of State Islamic University (UIN) Jurai Siwo Lampung. The core issue lies in the misalignment between graduate profiles and the demands of the modern job market, stemming from a lack of a data-driven evaluation mechanism, minimal collaboration with the private sector, and a slow bureaucratic process. This paper utilizes a qualitative methodology and a systemic approach, beginning with a causal analysis to map the root problems, followed by the formulation and analysis of five strategic policy alternatives. These alternatives are crafted as formal regulations, such as ministerial decrees and circulars, to ensure their binding and sustainable implementation. A comparative analysis utilizing a structured scoring method was then applied to identify the most effective policy alternative. The findings suggest that the optimal solution is a regulation mandating the implementation of an integrated data management system and the decentralization of curriculum change authority. The recommendations aim to provide practical guidance for policymakers at both the university level and the Directorate General of Islamic Education of the Ministry of Religious Affairs. It is anticipated that implementing this policy will transform UIN Jurai Siwo Lampung into an institution that is responsive to industry dynamics, thereby enhancing graduate employability in the job market and optimizing the contribution of Islamic higher education to national human capital development.